The influence of carotid plaque on carotid artery stiffness indicators in hypertensive patients with and without accompanying type 2 diabetes - V. V. Syvolap; A. O. Bohun (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. To compare the elastic properties of the common carotid arteries (CCA) in patients with stage II hypertension (HTN) depending on the presence of diabetes mellitus (DM) and atherosclerotic plaque (ASP) <50 % of carotid arteries (CA).